Compatibility of pentoxifylline and parenteral medications - Campbell, A.L.; Petrovski, M.; Senarathna, S.G.; Mukadam, N.; Strunk, T.; Batty, Kevin (BMJ PUBLISHING GROUP, 2020)
Objective: To investigate the physical and chemical compatibility of pentoxifylline (PTX) with a range of parenteral medications used in neonatal intensive care.